Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae - Ribeiro-Júnior, Marco A.; Amaral, Silvana (Zootaxa, 2017)
We present distribution data of all Alopoglossidae and Gymnophthalmidae lizards known from the Brazilian Amazonia, totaling 54 species-level taxa, belonging to 17 genera and two families. This represents 22 more species-level taxa than previously reported. Data were based on 17,431 specimens deposited in three North American and eight Brazilian museums, including the main collections harboring Amazonian material. Most species ( 80%) are endemic to Amazonia; non-endemic species are mainly associated with open vegetation (savanna) enclaves or open dry (semideciduous) forest in Amazonia, with a few exceptions. As a whole, seven taxa (including one species complex) are widespread in Amazonia, six are restricted to eastern Amazonia, seven to western Amazonia, two to southwestern Amazonia, 11 to southern Amazonia, 11 to northern Amazonia (either in part of it or widespread in the Guiana region), and six to the southern peripheral portion of Amazonia. Besides, four species present unique distributions. Considering this study and the other three catalogues of distribution of lizards already published, the total number of lizard species from Brazilian Amazonia increased from 97 to 142 species-level tava. It represents an increase of 45 species from the region since the last revision.